Impacts of electrokinetic isolation of phosphorus through pore water drainage on sediment phosphorus storage dynamics. (November 2020) - Tang, Xianqiang; Li, Rui; Han, Ding; Wu, Xingyi
Abstract: Pore water is a crucial storage medium and a key source of sediment phosphorus. A novel equipment based on electrokinetic geosynthetics (EKGs) was used for isolating phosphorus from eutrophic lake sediments through pore water drainage. Three mutually independent indoor group experiments (A, B, and C) were conducted to investigate the effects of voltage gradient (0.00, 0.25, and 0.50 V/cm) on pore water drainage capacity, phosphorus removal performance, sediment physicochemical properties, and phosphorus storage dynamics. The average reduction in the sediment moisture and total phosphorus content was 2.5%, 4.3%, and 4.6% and 28.15, 75.95, and 112.65 mg/kg after 6 days of treatment for A, B and C, respectively. Efficient pore water drainage through gravity and electroosmotic flow and electromigration of phosphate were the main drivers of sediment-dissolved and mobilized phosphorus separation. A high voltage gradient facilitated the migration of pore water and the phosphorus in it. The maximal effluent total phosphorous (TP) concentration was up to 27.9 times that in the initial pore water samples, and negligible effluent TP was detected when the pore water pH was less than 2.5. The TP concentration was exponentially and linearly related to the pH and electronic conductivity of the electroosmotic flow, respectively. The migration of H + within the sediment matrix promoted the liberation of metals bounded to phosphorus, particularly of Ca–P and Fe–P. Pore water drainage through an EKG resulted in Ex–P separation of up to 87.50% and a 13.84 mg/kg decrease in Ca–P and 125.35 mg/kg accumulation of low mobile Fe–P in the weak acid anode zone. Graphical abstract: Image 1 Highlights: Pore water drainage through EKG reduced sediment phosphorus bioavailability. Negligible phosphorus was separated when pore water pH was less than 2.5 Phosphorus separation was linearly related to the EC of electroosmotic flow. Sediment amorphous irons oxides were reduced in the cathode zone.